Enhanced B‐cell differentiation driven by advanced cirrhosis resulting in hyperglobulinemia. Issue 9 (13th March 2018) - Doi, Hiroyoshi; Hayashi, Eiichi; Arai, Jun; Tojo, Masayuki; Morikawa, Kenichi; Eguchi, Junichi; Ito, Takayoshi; Kanto, Tatsuya; Kaplan, David E; Yoshida, Hitoshi
Abstract: Background and Aim: The mechanism underlying hyperglobulinemia in cirrhosis, a long appreciated phenomenon, has never been clearly understood. The aim of this study is to investigate the basis for changes in humoral immunity observed in cirrhosis. Methods: We retrospectively reviewed our medical record to analyze serum immunoglobulin (Ig) levels in patients with liver disease. We also prospectively analyzed peripheral blood mononuclear cells and sera from liver disease patients. Peripheral blood mononuclear cell surface marker expressions were measured by flow cytometry and serum B‐cell‐activating factor was measured by enzyme‐linked immunosorbent assay. Expression of specific gene expression in magnetically separated B cells was also analyzed by real‐time polymerase chain reaction. Results: In retrospective analysis, we found that advancing cirrhosis, irrespective of underlying etiology or hepatocellular carcinoma, resulted in progressively increasing levels of serum IgG and IgA. In prospective analysis using clinical samples, we demonstrated that advancing cirrhosis stage was associated with increased toll‐like‐receptor (TLR)9 expression in CD27 + B cell and serum B‐cell‐activating factor levels but decreased CD27 + memory B‐cell frequency. The remaining CD27 + B cells in peripheral blood exhibited increased activation‐induced cytidine deaminase mRNA expression. Finally, we also demonstrated isolated B cells from advanced cirrhosis were more reactive to TLR9 stimulation that drove antibody secreting cells differentiation leading to hyperimmunoglobulinemia in vitro . Conclusions: Enhanced TLR9‐induced differentiation into antibody secreting cell may explain peripheral reductions of circulating CD27 + memory B cells as well as increased serum Ig levels in cirrhosis.